2016
DOI: 10.4269/ajtmh.15-0422
|View full text |Cite
|
Sign up to set email alerts
|

Severe Dengue Fever Outbreak in Taiwan

Abstract: Abstract. Dengue fever (DF) is a vector-borne disease caused by dengue viruses (DENVs). Epidemic dengue occurs intermittently in Taiwan. In 2014, Taiwan experienced its largest DF outbreak. There were 15,732 DF cases reported. There were a total of 136 dengue hemorrhagic fever (DHF) cases, of which 20 resulted in death. Most DF cases were reported in southern Taiwan. A total of 15,043 (96%) cases were from Kaohsiung, a modern city in southern Taiwan. This report reviews DF epidemics in Taiwan during [2005][200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
56
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 17 publications
1
56
0
3
Order By: Relevance
“…4 We previously reported a correlation between the underground pipeline leaking gas explosion event, which was followed by continuous heavy rains, with the 2014 DF outbreak in Kaohsiung ( P <0.0001; r =0.87). 5 The cavities created by the explosion might have led to an increase in stagnant waters suitable for breeding of the Aedes mosquitoes. We found that the Breteau index for measuring the density of mosquitoes increased from 10%–19% to 35%–49% from July to September in Kaohsiung.…”
mentioning
confidence: 99%
“…4 We previously reported a correlation between the underground pipeline leaking gas explosion event, which was followed by continuous heavy rains, with the 2014 DF outbreak in Kaohsiung ( P <0.0001; r =0.87). 5 The cavities created by the explosion might have led to an increase in stagnant waters suitable for breeding of the Aedes mosquitoes. We found that the Breteau index for measuring the density of mosquitoes increased from 10%–19% to 35%–49% from July to September in Kaohsiung.…”
mentioning
confidence: 99%
“…6 This unique epidemiologic pattern has been unchanged in the past decade, with annual numbers of fatal cases ranging from 0 to 7. 7 However, in 2014, an unprecedented dengue outbreak, involving more than 15,000 infections, including 136 DHF cases and 20 fatalities, occurred, 8 followed by an even larger outbreak in 2015. These outbreaks suggest that dengue may have become endemic to Taiwan and that occurrence of tens of thousands of DENV infections annually might be not uncommon in future.…”
Section: Introductionmentioning
confidence: 99%
“…Imported dengue has also caused local outbreaks in the United States and Japan [8,9]. Imported dengue fever cases frequently caused disastrous epidemics with thousands of patients in Taiwan [10,11]. Previous studies in Taiwan have revealed that a systematic approach to identifying infected passengers could minimize the risk of local transmissions of virus and outbreaks [12,13].…”
Section: Introductionmentioning
confidence: 99%